PROSPECTS OF APPLICATION THE THERMAL TECHNOLOGIES FOR MODERN SEWING PRODUCTION - SYROTENKO, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The widespread use of a range of synthetic textile materials for diferent types of clothing contributes to the relevance of the use of thermal technologies for light industry enterprises. Today they are used for various processes of garment production. For cutting, automated cutting complexes are used, in which parts are cut using a laser or plasma. For single cutting, laser installations are used, which, in addition to cutting, are capable to decorate clothes by engraving parts. For joining parts, seamless technologies are used, which are based on the process of welding synthetic materials under the influence of ultrasound, or on the process of gluing parts using thermal tape, which is also used to seal seams in clothing with water-repellent properties. For finishing clothes, sublimation, thermal transfer printing and silk-screen printing technologies are used, which work on the principle of polymerization of thermal paints, which, under the influence of temperature and pressure, are able to penetrate the inside of materials and form a strong connection that is not damaged during operation. Since the range of thermal equipment is very large and has certain features of application for different processes and materials, it is necessary to study their technical characteristics and choose more cost-effective offers for sewing enterprises of various types of activity. The article considers a list of thermal equipment related to the use of laser, plasma, thermal transfer and ultrasonic principles of action. The most common brands and suppliers of this equipment on the Ukrainian market was analyzed. A descriptive characteristic of the features of the operation of thermal equipment at different stages of clothing manufacturing is given. A comparative characteristic of the technical parameters of equipment of different models and manufacturers is given. Their latest technological solutions was indicated and the cost of equipment of different price groups. The most cost-effective types of equipment for enterprises of various types of activity are recommended. The analysis shows a wide range of modern thermal equipment for sewing enterprises, which allows you to freely select the desired option. The primary factor in this case is the manufacturer’s brand, model of equipment and its cost. The feasibility of using advanced thermal technologies for clothing processing ensures time savings, improved product processing quality, and achievement of world-class clothing manufacturing.